2009
DOI: 10.1007/s11105-009-0089-0
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary Multi-gene Reference for Normalization of Real-Time PCR Gene Expression Data

Abstract: Analysis of gene expression using real-time reverse transcription polymerase chain reaction (RT-PCR) requires reference genes to normalize expression values between samples. We have developed a novel reference for real-time RT-PCR using an arbitrary primer to amplify a random set of genes. The arbitrary primer amplifies over 30 genes, whose cumulative expression as measured by real-time RT-PCR closely follows that of UBQ 11, an Arabidopsis thaliana gene that is used as a reference on microarrays. The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…PCR exponentially amplifies a small starting quantity of cDNA to a large amount of DNA product; in fact, even seemingly insignificant technical variability before amplification can lead to considerable errors in the end product, although this is less of a concern in RT-qPCR than in conventional RT-PCR. To overcome this limitation, researchers typically normalized the mRNA expression of their genes of interest to the expression of a constitutively expressed reference gene (Udvardi et al 2008), and new reference genes are being considered, including synthetic templates and random oligoprimers (Phillips et al 2009;Tai et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…PCR exponentially amplifies a small starting quantity of cDNA to a large amount of DNA product; in fact, even seemingly insignificant technical variability before amplification can lead to considerable errors in the end product, although this is less of a concern in RT-qPCR than in conventional RT-PCR. To overcome this limitation, researchers typically normalized the mRNA expression of their genes of interest to the expression of a constitutively expressed reference gene (Udvardi et al 2008), and new reference genes are being considered, including synthetic templates and random oligoprimers (Phillips et al 2009;Tai et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Quantitative real-time polymerase chain reaction, a precise method to measure changes in the gene transcription level, has been widely used in recent years (Remans et al 2008;Phillips et al 2009;Tai et al 2009;Qi et al 2010). The upregulated expression pattern of the MxbHLH01 gene was similar to that of AtFRU accumulating to high levels under iron-deficient conditions in roots (Jakoby et al 2004), but this pattern was different from that of LeFER, which was reported to be independent of the iron supply (Ling et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The 27 genes included 5 housekeeping genes and 22 experimental genes ( Table 1). The five housekeeping genes were adenine phosphoribosyl transferase (aprt), tubulin, cyclophilin (Nicot et al 2005;Tai et al 2009), elongation factor 1-α(ef1α) (Nakane et al 2003) and COX1 (Quiñones et al 1995;Li et al 1996). The test genes are described in Table 1.…”
Section: Rna Extraction and Quantification Of Gene Expressionmentioning
confidence: 99%